Dominasi Istri Pencari Nafkah Utama dalam Keluarga - Zakiyyah, Naili; Suharto, Mukhamad (Qanun: Jurnal Hukum Keluarga Islam, 2023)
Many wives become Women Workers (TKW) while husbands at home are odd-job workers, which in turn can have negative implications starting from family conflict, less than optimal care for children to divorce. This study aims to describe the dominance of the wife's role as the main breadwinner to meet the economic needs of her family. Especially what happened in Cangkuang Village, Babakan District, Cirebon Regency. The problem formulated is limited to why the main breadwinner wife is so dominant and how the sociology of law reviews the role shift that occurs. This research is field research, descriptive analytical in nature and uses a normative sociological approach with the intention that the knowledge and description of the role of the main breadwinner wife becomes clear. From the research findings, 60% of informants in Cangkuang Village are the main breadwinners because they want to meet the needs of the family, while the husband is a freelance worker. From the optics of Legal Sociology, it emphasizes that the wife's role is dominated by the element of "adaptation," where economic needs that must be met are social facts. This is then followed by positive and negative impacts. On the positive side, the family economy can be fulfilled and children learn to live independently. On the negative side, there is a pattern of husband and wife relationships that are full of conflicts that lead to divorce or less harmonious relationships between close relatives and can adversely affect the behavior of children as well as their educational development because the care of their mothers is not fulfilled optimally. Then from a normative point of view, it can be explained that if the wife works as a migrant worker and the husband is pleased, then according to the Marriage Law the husband is still obliged to provide maintenance as long as the wife is not disobedient or nusyuz.